Automatic quality measurement for health information on the internet. (1st January 2014) - Liu, Rey-Long
The internet has been a main source from which healthcare consumers get health information. Quality of the health information is thus essential, since improper health information may cause serious damage to human life. However measurement of the quality is challenging since the quality is correlated with many factors that are difficult to quantitatively measure and integrate. In this paper, we propose a technique SPA to measure the quality of the health information in any given webpage. SPA employs a quality indicator, named health information concentration, which is defined to be the amount of different health terms in the largest passage that mainly contains those terms that are correlated to health. Experiments on thousands of real-world web pages are conducted to evaluate SPA. The results show that SPA can rank high those web pages that are judged to be high-quality by ethical quality standards and readers' credibility perceptions. SPA can thus work with search engines to help healthcare consumers to access both quality and relevant passages for specific health information needs.